High-frequency low-loss three-dimensional shielding material and preparation method thereof
Through the combination of annealing crystallization treatment of iron-based nanocrystalline and amorphous materials and ferrite powder, a high-frequency and low-loss three-dimensional shielding material was prepared, solving the problems of traditional materials' heat generation and insufficient magnetic induction during high-frequency wireless charging. , realizes more efficient power conversion and is suitable for applications in three-dimensional shapes.
Patent Information
- Application Number
- CN202411797256.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Traditional nanocrystal magnetic insulation materials generate severe heat during high-frequency wireless charging, and ferrite materials have low saturation magnetic induction in large current scenarios, making them difficult to be suitable for three-dimensional and curved surface needs. The composite material preparation process is complex and costly.
The nanocrystalline and/or amorphous materials are crushed or powdered and annealed and crystallized to obtain nanocrystalline soft magnetic alloy powder and ferrite powder and molded by molding or injection molding to prepare a high frequency and low loss three-dimensional body Shielding material.
The combination of the high saturation flux density of nanocrystals and the low loss characteristics of ferrite is achieved, which reduces leakage magnetic loss, improves the efficiency of electric energy conversion, and is suitable for applications in three-dimensional shapes.
Smart Images

Figure CN119296947A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of wireless charging, and in particular relates to a high-frequency low-loss three-dimensional shielding material and a preparation method thereof. Background Art
[0002] With the gradual increase of wireless charging power, the traditional nanocrystalline magnetic insulation material has a large high-frequency eddy current loss due to its low resistivity, resulting in more serious heating when used in high-frequency wireless charging modules; in addition, although the traditional ferrite material has a small high-frequency eddy current loss, its saturation magnetic induction is low, and its application is limited in high-current scenarios with large charging power. It is a feasible solution to combine the advantages of nanocrystalline magnetic insulation materials with ferrite magnetic insulation materials. For example, patent CN 116417226 A discloses a magnetic insulation composite material for wireless charging, which includes a ferrite magnetic insulation material layer and a nanocrystalline magnetic insulation material layer stacked, wherein the nanocrystalline magnetic insulation material layer includes at least one multilayer nanocrystalline magnetic insulation material, and the magnetic permeability of the multilayer nanocrystalline magnetic insulation material gradually increases in the direction away from the ferrite magnetic insulation material layer. The magnetic insulation composite material for wireless charging with the above structure can greatly reduce the eddy current loss and heat generation during high-power charging, thereby enabling it to have better power transmission efficiency during application. However, this multilayer structure is not conducive to the development of miniaturization and lightweight of devices; at the same time, the nanocrystalline tape insulation material is relatively brittle and has poor toughness, and its structure is relatively simple, making it difficult to apply to three-dimensional and curved usage scenarios.
[0003] Patent CN 102142309 A discloses a bulk amorphous / ferrite soft magnetic composite material, which is an amorphous / ferrite soft magnetic composite material with a three-dimensional honeycomb structure. The nest wall structure is composed of high-resistivity soft magnetic ferrite. The nest wall ferrite surrounds and completely isolates the amorphous alloy soft magnetic phase composed of soft magnetic amorphous alloy particles in the nest, so that the amorphous alloy soft magnetic phases in the nest are insulated from each other. The resistivity of the composite material is significantly improved compared with the amorphous alloy soft magnetic material, and the working frequency of the amorphous alloy is improved. However, the preparation process of the composite material requires that the soft magnetic ferrite powder is completely and evenly coated on the surface of the soft magnetic amorphous alloy particles, and the spark plasma sintering technology needs to be used. The requirements for process control and equipment are high, and it is difficult to stabilize and mass produce, and the cost is high.
[0004] Patent CN 115762949 A discloses a high permeability and low loss iron-based soft magnetic composite material, which includes a matrix material and an insulating medium. Garnet-type ferrite RIG is used to insulate and coat amorphous nanocrystalline and other magnetic powders, which can effectively isolate particle contact and reduce magnetic loss. However, the composite material needs to use a specific garnet-type ferrite RIG, and the range of raw material sources is relatively narrow. Summary of the invention
[0005] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a method for preparing a high-frequency, low-loss three-dimensional shielding material.
[0006] Another object of the present invention is to provide a high-frequency, low-loss three-dimensional shielding material prepared by the above method.
[0007] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a high-frequency low-loss three-dimensional shielding material, comprising the following preparation steps: (1) The composition is Fe bal. M a Cu b M' c Si d B e X f The iron-based nanocrystalline and / or amorphous material is crushed or powdered, and then annealed and crystallized to obtain nanocrystalline soft magnetic alloy powder; wherein M is Co and / or Ni, M' is at least one of Nb, V, Ta, and Mo, and X is at least one of common impurity elements such as C, O, N, S, and P; a=0~30%, b=0~2%, c=0~7%, d=5~18%, e=5~15%, and f=0~0.5%; (2) The obtained nanocrystalline soft magnetic alloy powder is mixed with ferrite powder and a binder and then subjected to compression molding or injection molding to obtain a high-frequency, low-loss three-dimensional shielding material.
[0008] Furthermore, in step (1), a=0~15%, b=0.5~1.5%, c=2~4%, d=12~17%, e=5~8%, and f=0~0.5%.
[0009] Furthermore, the crushing in step (1) refers to preparing the iron-based nanocrystalline and / or amorphous strip into flaky powder with a thickness of 0.005-0.03 mm and a size of 0.05-5 mm by mechanical crushing.
[0010] Furthermore, the powder making in step (1) refers to directly preparing the iron-based nanocrystalline and / or amorphous alloy into spherical powder with a D50 particle size of 0.003-0.100 mm by water atomization, gas atomization, or water-gas combined atomization.
[0011] Furthermore, the temperature of the annealing crystallization treatment in step (1) is 500-620° C., and the time is 0.5-4 h.
[0012] Furthermore, the ferrite in step (2) is one or more of manganese-zinc ferrite, nickel-zinc ferrite and copper-zinc ferrite.
[0013] Furthermore, the ferrite powder in step (2) is a spherical powder with a D50 particle size of 0.003-0.100 mm.
[0014] Further preferably, the nanocrystalline soft magnetic alloy powder in step (2) is a flake powder with a thickness of 0.005-0.03 mm and a size of 0.05-0.5 mm; and the ferrite powder is a spherical powder with a D50 particle size of 0.003-0.100 mm.
[0015] Furthermore, the adhesive in step (2) is one or more of epoxy resin, low melting point glass, acrylic resin, silicone rubber, and polyurethane.
[0016] Furthermore, in step (2), the mass ratio of the nanocrystalline soft magnetic alloy powder, the ferrite powder and the binder is 100:1~30:1~10.
[0017] Furthermore, the compression molding in step (2) has a pressure of 5-500 MPa, a temperature of 25-200° C., and a time of 0.2 s-3 s; and the injection molding refers to extruding the mixed material into a mold by screw extrusion.
[0018] Furthermore, the material formed in step (2) is in the shape of a plane, a curved surface or a three-dimensional structure.
[0019] A high-frequency, low-loss three-dimensional shielding material is prepared by the above method.
[0020] Furthermore, a coil fitting area is provided on one side of the three-dimensional shielding material, and the outer periphery and inner periphery of the coil fitting area have raised portions perpendicular to the coil plane.
[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The composite shielding material obtained by the present invention can have both the high saturation magnetic flux density of nanocrystals and the low loss characteristics of ferrite, and can be processed into a three-dimensional shape to reduce leakage flux in the XY direction, reduce leakage flux loss, and improve power conversion efficiency.
[0022] (2) The present invention further uses flaky nanocrystalline soft magnetic alloy powder and spherical ferrite powder to compound, which can more effectively block the eddy current path between the nanocrystalline soft magnetic alloy particles and better couple the magnetic field between the nanocrystalline soft magnetic alloy particles, thereby achieving better high-frequency magnetic properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the appearance structure of the high-frequency low-loss three-dimensional shielding material obtained in Examples 1 to 5 and Comparative Examples 1 to 2.
[0024] Figure 2 This is a schematic diagram of the appearance structure of the layered nanocrystalline shielding material obtained in Comparative Example 3. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto. Example 1
[0026] A method for preparing a high-frequency low-loss three-dimensional shielding material, comprising the following preparation steps: (1) The composition is Fe 73.5 Cu1Nb3Si 15.5 The iron-based amorphous alloy with a content of B7 (at.%) was prepared into spherical powder with a D50 particle size of 0.10 mm by water-gas combined atomization, and then heated to 580°C for annealing and crystallization treatment for 2.5 h to obtain nanocrystalline soft magnetic alloy powder.
[0027] (2) The obtained nanocrystalline soft magnetic alloy powder is mixed with spherical manganese-zinc ferrite powder with a D50 particle size of 0.10 mm and a binder (low-melting point glass and epoxy resin in a mass ratio of 1:2) and then compression molded at a pressure of 30 MPa and a temperature of 100°C for 0.5 s; the mass ratio of the nanocrystalline soft magnetic alloy powder, ferrite powder and binder is 100:15:3 to obtain a high-frequency, low-loss three-dimensional shielding material. A coil bonding area is set on one side of the obtained three-dimensional shielding material, and the outer and inner peripheries of the coil bonding area have raised portions perpendicular to the coil plane. The schematic diagram of its external structure is shown as follows Figure 1 shown. Example 2
[0028] A method for preparing a high-frequency low-loss three-dimensional shielding material, comprising the following preparation steps: (1) The composition is Fe 73.5 Cu1Nb3Si 15.5 The iron-based amorphous alloy with a content of B7 (at.%) was prepared into spherical powder with a D50 particle size of 0.02 mm by water-gas combined atomization, and then heated to 580°C for annealing and crystallization treatment for 2.5 h to obtain nanocrystalline soft magnetic alloy powder.
[0029] (2) The obtained nanocrystalline soft magnetic alloy powder is mixed with spherical manganese-zinc ferrite powder with a D50 particle size of 0.02 mm and a binder (low-melting-point glass and epoxy resin in a mass ratio of 1:2) and then molded at a pressure of 30 MPa and a temperature of 100°C for 0.5 s; the mass ratio of the nanocrystalline soft magnetic alloy powder, ferrite powder and binder is 100:15:3, and a high-frequency low-loss three-dimensional shielding material is obtained. The schematic diagram of the appearance structure of the obtained three-dimensional shielding material is shown in the figure Figure 1 shown. Example 3
[0030] A method for preparing a high-frequency low-loss three-dimensional shielding material, comprising the following preparation steps: (1) The composition is Fe 73.5 Cu1Nb3Si 15.5 The iron-based amorphous alloy with a content of B7 (at.%) was prepared into spherical powder with a D50 particle size of 0.05 mm by water-gas combined atomization, and then heated to 550°C for annealing and crystallization treatment for 3 h to obtain nanocrystalline soft magnetic alloy powder.
[0031] (2) The obtained nanocrystalline soft magnetic alloy powder is mixed with spherical nickel-zinc ferrite powder with a D50 particle size of 0.05 mm and a binder (low-melting point glass and epoxy resin in a mass ratio of 1:2) and then molded at a pressure of 50 MPa and a temperature of 100°C for 1 second; the mass ratio of the nanocrystalline soft magnetic alloy powder, ferrite powder and binder is 100:10:3, and a high-frequency low-loss three-dimensional shielding material is obtained. The schematic diagram of the appearance structure of the obtained three-dimensional shielding material is shown in the figure Figure 1 shown. Example 4
[0032] A method for preparing a high-frequency low-loss three-dimensional shielding material, comprising the following preparation steps: (1) The composition is Fe 73.5 Cu1Nb3Si 15.5 The iron-based amorphous alloy with a content of B7 (at.%) was prepared into spherical powder with a D50 particle size of 0.02 mm by water-gas combined atomization, and then heated to 520°C for annealing and crystallization treatment for 4 h to obtain nanocrystalline soft magnetic alloy powder.
[0033] (2) The obtained nanocrystalline soft magnetic alloy powder is mixed with spherical copper-zinc ferrite powder with a D50 particle size of 0.02 mm and a binder (low-melting point glass and epoxy resin in a mass ratio of 1:2) and then molded at a pressure of 20 MPa and a temperature of 100°C for 2 seconds; the mass ratio of the nanocrystalline soft magnetic alloy powder, ferrite powder and binder is 100:1:3, and a high-frequency low-loss three-dimensional shielding material is obtained. The schematic diagram of the appearance structure of the obtained three-dimensional shielding material is shown in the figure Figure 1 shown. Example 5
[0034] A method for preparing a high-frequency low-loss three-dimensional shielding material, comprising the following preparation steps: (1) The composition is Fe 73.5 Cu1Nb3Si 15.5The alloy with B7 (at.%) was prepared into an amorphous alloy strip with a thickness of 20 μm by single-roll rapid quenching method; then it was prepared into a flake powder with a thickness of 0.02 mm and a size of 0.1 mm by mechanical crushing and screening. Then it was heated to 580°C for annealing and crystallization treatment for 2.5 hours to obtain nanocrystalline soft magnetic alloy powder.
[0035] (2) The obtained nanocrystalline soft magnetic alloy powder is mixed with spherical manganese-zinc ferrite powder with a D50 particle size of 0.02 mm and a binder (low-melting-point glass and epoxy resin in a mass ratio of 1:2) and then molded at a pressure of 30 MPa and a temperature of 100°C for 0.5 seconds. The mass ratio of the nanocrystalline soft magnetic alloy powder, ferrite powder and binder is 100:15:3 to obtain a high-frequency low-loss three-dimensional shielding material. The schematic diagram of the appearance structure of the obtained three-dimensional shielding material is shown in the figure. Figure 1 shown.
[0036] Comparative Example 1 A method for preparing a high-frequency low-loss three-dimensional shielding material, comprising the following preparation steps: Spherical manganese zinc ferrite powder with a D50 particle size of 0.10 mm and a binder (low melting point glass and epoxy resin in a mass ratio of 1:2) were mixed and molded at a pressure of 30 MPa, a temperature of 100°C, and the pressure was maintained for 0.5 seconds; the mass ratio of manganese zinc ferrite powder and binder was 115:3, and a high-frequency low-loss three-dimensional shielding material was obtained. The schematic diagram of the appearance structure of the obtained three-dimensional shielding material is shown in the figure Figure 1 shown.
[0037] Comparative Example 2 A method for preparing a high-frequency low-loss three-dimensional shielding material, comprising the following preparation steps: (1) The composition is Fe 73.5 Cu1Nb3Si 15.5 The iron-based amorphous alloy with a content of B7 (at.%) was prepared into spherical powder with a D50 particle size of 0.10 mm by water-gas combined atomization, and then heated to 580°C for annealing and crystallization treatment for 2.5 h to obtain nanocrystalline soft magnetic alloy powder.
[0038] (2) Mix the obtained nanocrystalline soft magnetic alloy powder with a binder (low melting point glass and epoxy resin in a mass ratio of 1:2) and then perform compression molding at a pressure of 30 MPa and a temperature of 100°C for 0.5 seconds; the mass ratio of the nanocrystalline soft magnetic alloy powder to the binder is 115:3, and a high-frequency low-loss three-dimensional shielding material is obtained. The schematic diagram of the appearance structure of the obtained three-dimensional shielding material is shown in the figure Figure 1 shown.
[0039] Comparative Example 3 A method for preparing a layered nanocrystalline shielding material comprises the following steps: (1) The composition is Fe 73.5 Cu1Nb3Si 15.5 The alloy with B7 (at.%) was prepared into an amorphous alloy ribbon with a thickness of 20 μm by single-roll rapid quenching. The obtained amorphous alloy ribbon was heated to 580°C for annealing and crystallization treatment for 2.5 hours to obtain a single-layer nanocrystalline ribbon.
[0040] (2) The annealed single-layer nanocrystalline ribbon is stacked in two layers, and the two layers are fixed by bonding with a substrate-free double-sided adhesive. The outermost layer is protected by a substrate-free double-sided adhesive coating process, wherein the thickness of the double-sided adhesive is 2 μm. The double-sided coated double-layer nanocrystalline ribbon is subjected to a magnetic crushing treatment, and then the magnetic crushing double-layer nanocrystalline ribbon is multi-layered to obtain a nanocrystalline magnetic isolation sheet with a main body thickness that is the same as the three-dimensional shielding material coil bonding area in Example 1. The schematic diagram of the appearance structure of the obtained nanocrystalline magnetic isolation sheet is shown in FIG. Figure 2 shown.
[0041] The saturation magnetic induction intensity Bs of the shielding materials obtained in the above Examples 1 to 5 and Comparative Examples 1 to 3, as well as the inductance Ls, induction resistance Rs and quality factor Q value at different frequencies after bonding with the induction coil were measured, and the results are shown in Table 1 below.
[0042] Table 1
[0043] It can be seen from the comparison results of the above Examples 1 to 4 and Comparative Examples 1 to 2 that the three-dimensional shielding material of the present invention, through the combination of nanocrystalline soft magnetic alloy powder and ferrite powder, has a significantly reduced corresponding induction resistance Rs value and a significantly improved quality factor Q value compared to simple ferrite powder and nanocrystalline soft magnetic alloy powder. It shows that the combination of nanocrystalline soft magnetic alloy powder and ferrite powder can significantly reduce high-frequency loss. It can be seen from the comparison results of Comparative Example 2 and Comparative Example 3 that the three-dimensional shielding material of the present invention can effectively reduce the leakage magnetic flux in the XY direction, reduce the leakage magnetic flux loss, and improve the power conversion efficiency compared to conventional layered nanocrystalline shielding materials. It can be seen from the comparison results of Example 5 and Examples 1 to 2 that the use of flaky nanocrystalline soft magnetic alloy powder and spherical ferrite powder for compounding can more effectively block the eddy current path between nanocrystalline soft magnetic alloy particles and can better couple the magnetic field between nanocrystalline soft magnetic alloy particles, thereby further reducing the loss and achieving better high-frequency magnetic properties.
[0044] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a high-frequency low-loss three-dimensional shielding material, characterized in that: The method comprises the following preparation steps: (1) The composition is Fe bal. M a Cu b M' c Si d B e X f The iron-based nanocrystalline and / or amorphous material is crushed or powdered, and then annealed and crystallized to obtain nanocrystalline soft magnetic alloy powder; wherein M is Co and / or Ni, M' is at least one of Nb, V, Ta, and Mo, and X is at least one of common impurity elements such as C, O, N, S, and P; a=0~30%, b=0~2%, c=0~7%, d=5~18%, e=5~15%, and f=0~0.5%; (2) The obtained nanocrystalline soft magnetic alloy powder is mixed with ferrite powder and a binder and then subjected to compression molding or injection molding to obtain a high-frequency, low-loss three-dimensional shielding material.
2. The method for preparing a high-frequency low-loss three-dimensional shielding material according to claim 1, characterized in that: In step (1), a=0~15%, b=0.5~1.5%, c=2~4%, d=12~17%, e=5~8%, and f=0~0.5%.
3. The method for preparing a high-frequency low-loss three-dimensional shielding material according to claim 1, characterized in that: The crushing in step (1) refers to mechanically crushing the iron-based nanocrystalline and / or amorphous strip into flaky powders with a thickness of 0.005-0.03 mm and a size of 0.05-5 mm.
4. The method for preparing a high-frequency low-loss three-dimensional shielding material according to claim 1, characterized in that: The powder making in step (1) refers to directly preparing the iron-based nanocrystalline and / or amorphous alloy into spherical powder with a D50 particle size of 0.003-0.100 mm by water atomization, gas atomization or water-gas combined atomization.
5. The method for preparing a high-frequency low-loss three-dimensional shielding material according to claim 1, characterized in that: The temperature of the annealing crystallization treatment in step (1) is 500-620°C and the time is 0.5-4h.
6. The method for preparing a high-frequency low-loss three-dimensional shielding material according to claim 1, characterized in that: The ferrite in step (2) is one or more of manganese zinc ferrite, nickel zinc ferrite and copper zinc ferrite.
7. The method for preparing a high-frequency low-loss three-dimensional shielding material according to claim 1, characterized in that: The ferrite powder in step (2) is a spherical powder with a D50 particle size of 0.003-0.100 mm.
8. The method for preparing a high-frequency low-loss three-dimensional shielding material according to claim 1, characterized in that: The nanocrystalline soft magnetic alloy powder in step (2) is a flake powder with a thickness of 0.005-0.03 mm and a size of 0.05-0.5 mm; the ferrite powder is a spherical powder with a D50 particle size of 0.003-0.100 mm.
9. The method for preparing a high-frequency low-loss three-dimensional shielding material according to claim 1, characterized in that: The adhesive in step (2) is one or more of epoxy resin, low melting point glass, acrylic resin, silicone rubber, and polyurethane.
10. The method for preparing a high-frequency low-loss three-dimensional shielding material according to claim 1, characterized in that: The mass ratio of the nanocrystalline soft magnetic alloy powder, ferrite powder and binder mixed in step (2) is 100:1~30:1~10.
11. The method for preparing a high-frequency low-loss three-dimensional shielding material according to claim 1, characterized in that: The compression molding in step (2) is performed under a pressure of 5-500 MPa, a temperature of 25-200°C, and a time of 0.2-3 s; the injection molding refers to extruding the mixed material into a mold by screw extrusion.
12. The method for preparing a high-frequency low-loss three-dimensional shielding material according to claim 1, characterized in that: The material formed in step (2) is in the shape of a plane, a curved surface or a three-dimensional structure.
13. A high-frequency low-loss three-dimensional shielding material, characterized in that: It is prepared by the method according to any one of claims 1 to 12.
14. The high-frequency low-loss three-dimensional shielding material according to claim 13, characterized in that: A coil fitting area is arranged on one side of the three-dimensional shielding material, and the outer periphery and inner periphery of the coil fitting area have convex parts perpendicular to the coil plane.
Citation Information
Patent Citations
Method for improving magnetic permeability and consumption of amorphous core and composite core prepared by same
CN101777407A
Composite electromagnetic wave absorbing material used for radio frequency identification of internet of things
CN102300446A
Amorphous mixed powder, corresponding finished powder, magnetic powder core and preparation method thereof
CN110808138A
Wireless power transmission module and installation method thereof
CN111009383A
Electromagnetic wave absorber
CN1926936A